The Stress Levels of Premature Infants' Parents and Related Factors in NICU - Abdelaziz Hendy PhD; Salma El-sayed PhD; Salma Bakry MD; Shimmaa M Mohammed PhD; Hossam Mohamed MD; Abdelmouttelb Abdelkawy MD; Rym Hassani PhD; Madeha A Abouelela PhD; Salwa Sayed MD (SAGE Publishing, 2024)
Introduction Parental stress related to their infants' hospitalization is a significant concern that affects both parents and their infants. Fathers' experiences tend to be understudied compared to mothers. Further research on fathers' stress levels is necessary. While parental stress has been correlated with infant health severity, the specific causes and risk factors contributing to heightened stress levels in parents of neonatal intensive care unit (NICU) infants are not yet fully understood and require further investigation. Objective This study aimed to examine the stress levels experienced by parents of premature infants in the NICU and to explore the factors associated with parental stress in this specific context. Methods A cross-sectional observational design was used to accomplish this study, which was carried out on 743 parents from nine different NICUs located in governmental hospitals across various locations in Egypt. We used characteristics of parents and premature infants, and Parent Stress Scale was used for data collection. Results A majority of parents reported experiencing high stress in the following domains: sight and sound (80.3%), infants' appearance (69%), and the parent-infant relationship (81.4%). Additionally, about three-quarters (73.6%) of parents experienced high stress overall, with a mean score of 167.56 (21.3). Conclusion About three-quarters of the parents experienced high overall stress levels. Also, factors that were found to affect parents' stress levels included premature infants connected to mechanical ventilators, previous neonatal death, parents living far from hospitals, infants delivered through cesarean section, insufficient income, and prolonged hospitalization beyond 5 days.